Mesenchymal Stromal Cell-Produced Components of Extracellular Matrix Potentiate Multipotent Stem Cell Response to Differentiation Stimuli - Novoseletskaya, Ekaterina; Grigorieva, Olga; Nimiritsky, Peter; Basalova, Nataliya; Eremichev, Roman; Milovskaya, Irina; Kulebyakin, Konstantin; Kulebyakina, Maria; Rodionov, Sergei; Omelyanenko, Nikolai; Efimenko, Anastasia (Frontiers in Cell and Developmental Biology, 2020)
Extracellular matrix (ECM) provides both structural support and dynamic microenvironment for cells regulating their behavior and fate. As a critical component of stem cell niche ECM maintains stem cells and activates their proliferation and differentiation under specific stimuli. Mesenchymal stem/stromal cells (MSCs) regulate tissue-specific stem cell functions locating in their immediate microenvironment and producing various bioactive factors, including ECM components. We evaluated the ability of MSC-produced ECM to restore stem and progenitor cell microenvironment in vitro and analyzed the possible mechanisms of its effects. Human MSC cell sheets were decellularized by different agents (detergents, enzymes, apoptosis inductors) to select the optimized combination (CHAPS and DNAse I) based on the conservation of decellularized ECM (dECM) structure and effectiveness of DNA removal. Prepared dECM was non-immunogenic, supported MSC proliferation and formation of larger colonies in CFU-assay. dECM effectively promoted MSC three lineage differentiation (adipogenic, osteogenic and chondrogenic) compared to plastic or plastic covered by selected ECM components (collagen, fibronectin, laminin). Interestingly, dECM produced by human fibroblasts could not enhance MSC differentiation like MSC-produced dECM, indicating cell-specific functionality of dECM. We demonstrated the significant integrin contribution in dECM-cell interaction by blocking the stimulatory effects of dECM with RGD peptide and suggested the involvement of key intracellular signaling pathways activation (pERK/ERK and pFAK/FAK axes, pYAP/YAP and beta-catenin) in the observed processes based on the results of inhibitory analysis. Taken together, we suppose that MSC-produced dECM may mimic stem cell niche components in vitro and maintain multipotent progenitor cells to insure their effective response to external differentiating stimuli upon activation. The obtained data provide more insights into the possible role of MSC-produced ECM in stem and progenitor cell regulation within their niches. Our results are also useful for the developing of dECM-based cell-free products for regenerative medicine.